Assessing the Role of Social Control in Criminal Policy on Grave Desecration in Bantul and Yogyakarta - Fuadi Isnawan (Dialogia Iuridica, 2026)
This study examines the phenomenon of juvenile delinquency, specifically the act of vandalizing graves, which not only violates the law but also undermines the social, cultural, and religious values within society. A legal approach alone is deemed insufficient to explain and prevent this phenomenon; therefore, a more comprehensive criminological perspective is required. This study aims to analyze the role of Hirschi’s Social Control Theory in explaining the causes and prevention efforts regarding juvenile delinquency. This study employs an empirical method using a legal sociology approach, along with data collection techniques through observation and literature review. The results indicate that weak social bonds within family, school, and community environments contribute to increased risks of deviant behavior among adolescents. Specifically, low emotional attachment, weak commitment to values and the future, lack of involvement in positive activities, and a weak belief in social norms and the law are the primary factors driving such behavior. Conversely, strengthening these four elements has been shown to effectively reduce the potential for juvenile delinquency through preventive measures; therefore, various approaches are needed to reinforce these elements so that adolescents can avoid such behavior. This study emphasizes that preventing juvenile delinquency is not sufficient through a legal approach alone but must be balanced with the comprehensive strengthening of social control in the daily lives of adolescents.